The Effectiveness of TikTok Social Media as a Mental Health Education Platform for Adolescents - Dian Priharja Putri; Lu’lu Atul Auliya; Septi Haryani; Yusiska Elvira Sanam; Yulia Suryani; Cindy Histavone; Wulan Septi Anggraeni; Chusnul Chotimah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Social media has become an important part of the lives of Generation Z and Alpha teenagers, as well as a potential medium for the dissemination of mental health information. Among various platforms, TikTok shows rapid growth with more than 63 million monthly active users in Indonesia in 2023, where 45% of its users are aged 13–24 years. The creative and easily accessible short video format makes TikTok an effective medium for mental health education, as evidenced by the popularity of the hashtag #mentalhealth which has been viewed more than 3.2 billion times from December 2019 to 2025. Knowing the effectiveness of TikTok social media as a medium for mental health education for adolescents. This study used a non-equivalent control group design. A total of 928 adolescents aged 10–19 from five regions were divided into two groups: those receiving mental health education through TikTok (n=464) and those receiving education through Instagram (n=464). Respondents' mental health knowledge was measured twice using questionnaires, before and after the health education was provided. Post-test results showed a significant increase in the TikTok group with a p-value <0.05, indicating a difference in knowledge before and after the intervention. The number of respondents in the high knowledge category increased, while the number of respondents in the low knowledge category decreased significantly. Education through short videos on TikTok is more effective in increasing adolescents' mental health knowledge. Delivering information that is visually engaging, concise, and tailored to adolescent communication styles is a key factor in its success.